2019
DOI: 10.1002/cctc.201801648
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of MeOH and Toluene into Styrene and Ethylbenzene Using Composite Catalysts Containing MeOH Dehydrogenation Components

Abstract: Scheme 1. Coupling reaction of methanol dehydrogenation and side-chain alkylation of toluene over composite catalysts. Na 2 B 4 O 7 and CsX were selected as model catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…It should be mentioned here that, although the catalytic activity of 0.15 Fe/CsX-I is lower than the literature-reported ZrB 2 O 5 -or BPO 4 -modified CsX catalysts [9,19], it is still a relatively active catalyst in comparison with other additive-modified CsX catalysts, like Cs 2 O/CsX [7], Na 2 B 4 O 7 /CsX [17], and ZnO/CsX [39], suggesting that Fe(NO 3 ) 3 could functionalize as an effective additive to improve the catalytic performance of the ion-exchanged CsX catalyst. A undesirable feature of the Fe(NO 3 ) 3 -modified CsX catalyst is that it exhibits relatively low selectivity to styrene, and high selectivity to ethylbenzene.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…It should be mentioned here that, although the catalytic activity of 0.15 Fe/CsX-I is lower than the literature-reported ZrB 2 O 5 -or BPO 4 -modified CsX catalysts [9,19], it is still a relatively active catalyst in comparison with other additive-modified CsX catalysts, like Cs 2 O/CsX [7], Na 2 B 4 O 7 /CsX [17], and ZnO/CsX [39], suggesting that Fe(NO 3 ) 3 could functionalize as an effective additive to improve the catalytic performance of the ion-exchanged CsX catalyst. A undesirable feature of the Fe(NO 3 ) 3 -modified CsX catalyst is that it exhibits relatively low selectivity to styrene, and high selectivity to ethylbenzene.…”
Section: Discussionmentioning
confidence: 61%
“…Hattori and coworkers reported that metal borate-modified CsX showed improved catalytic activity and selectivity compared to styrene owning to the ability of borates to selectively form formaldehyde from methanol [7,9]. Han et al [17] gave a similar speculation after studying the side-chain alkylation reaction over composite catalysts composed of CsX and sodium borate (Na 2 B 4 O 7 ) or CuO/SiO 2 . In another work reported by Wieland et al [2], they proposed that impregnating boric acid on CsX could effectively promote the side-chain alkylation activity by neutralizing some unfavorable strong basic sites, which are the main active centers for rapidly decomposing methanol to byproducts like CO and H 2.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…3(a)) [24]. The produced formaldehyde acts as the actual alkylating reagent [25]. During alkylation, a couple of side-reactions occur.…”
Section: Side-chain Alkylation Of Toluene With Methanolmentioning
confidence: 99%